The Influence of 1-Triacontanol on the growth, flowering, and quality of potted bougainvillea plants (Bougainvillea glabra var. "Elizabeth Angus'') under natural conditions - Khandaker, M.M.; Faruq, G.; Rahman, M.M.; Sofian-Azirun, Mohd; Boyce, A.N. (2013)
Selected physiological and biochemical parameters were monitored at the vegetative and reproductive growth stages in potted Bougainvillea plants treated with five different concentrations of TRIA. Advanced flowering, flower bud number, and blooming rate increased significantly with 0.5 and 1.0 mg/L TRIA treatments. Similarly, photosynthetic rate, pigment content, quantum yield, and stomatal conductance increased significantly with 2.5, 1.0, and 5.0 mg/L TRIA treatments. Higher levels of N, P, and K, as well as increased total soluble solids (TSS) and higher sugar and protein contents, were recorded in treated plants. Furthermore, 46 more flowers, a 1.5-fold increase in bract weight, increased longevity, and 40 less leaf abscission were recorded following 2.5 mg/L TRIA treatment. Phenol and flavonoid contents, sucrose phosphate synthase (SPS), and antioxidant activities were also markedly increased with 2.5 and 1.0 mg/L TRIA treatments. However, ethylene production was significantly lower in the treated plants. Positive correlations were observed between leaf TSS and flowering time and flower number, between leaf sugar content and bract weight, and between net photosynthesis and bract growth and dry matter production. It can be concluded that the foliar spray of TRIA stimulates growth, enhances flowering, and improves the quality of potted Bougainvillea plants.